INSIDENSI PENYAKIT BUSUK BUAH PADA TANAMAN PALA (Myristica fragrans H) DI KECAMATAN LEMBEH SELATAN ( - Yunita S. Najoan; Max M. Ratulangi; Emmy Senewe (Universitas Sam Ratulangi, 2016)
ABSTRACTThis research aims to study the incidence of black pod disease in plants nutmeg (Myristica fragrans H) in the district of South Lembeh for 3 months ie from January to April 2015. Laboratory studies conducted at the Laboratory of Microbiology and Plant Pathology, Faculty of Agriculture Unsrat Manado and in the field, namely in Subdistrict South Lembeh.Research in the laboratory to determine the fungal pathogen nutmeg pod disease while in the field to determine the incidence of the disease is carried out in the village Papusungan, Kelapa Dua village, village Mawali. To study the incidence of the disease by the method of survey and sampling deliberate on nutmeg experiencing symptoms of dry rot and wet rot.Dried fruit rot disease symptoms in the nutmeg that is, the fruit of pain at first seem small, round spots, the center line of approximately 0.3 cm, this part is brown and settles (concave). The results showed that the characteristic of fungal pathogens causing rot diseases dried fruit on nutmeg in District Lembeh Southern namely Stigmina myristicae, observation of this fungus directly seen in the fruit field diseased fruit rot dried and identified under a microscope. the symptoms of fruit rot disease wet first emerged at the base of the fruit, the affected part color becomes brown, spotting developments rapidly that within a few days its center line has reached 2.5 cm, fruit ill not be concave. the disease is caused by the fungus Colletotrichum gloeosporioides, this fungus konidium greenish brown, oval-shaped.The results of the study the incidence of rot diseases caused by pathogenic fungi, in the field there is a difference incidence of black pod disease caused by a fungal pathogen at different locations, highest average incidence of dried fruit rot 7.90%, and 12.27% wet rot.Key Words : Incidence, Rotten Fruit , Nutmeg